Characterisation of the onset and severity of adrenal and thyroid dysfunction associated with CTLA4-related hypophysitis. Issue 1 (2nd December 2021) - Seejore, Khyatisha; Giannoudi, Marilena; Osborn, Djoah; Lynch, Julie M; Al-Qaissi, Ahmed; Dunwoodie, Elaine; Hook, Jane; Marples, Maria; Murray, Robert D
Abstract: Context: The use of the CTLA4 inhibitor, ipilimumab, has proven efficacious in the treatment of melanoma, renal carcinoma and non-small cell lung cancer; however, it is associated with frequent immune-related adverse events (irAE). Ipilimumab-induced hypophysitis (IIH) is a well-recognised and not infrequent endocrine irAE. Objective: To investigate the timing of onset and severity of adrenal and thyroid hormone dysfunction around the development of IIH in patients treated for melanoma. Design: Aretrospective review of hormone levels in consecutive adult patients treated with ipilimumab (3 mg/kg) for advanced melanoma as monotherapy or in combination with a PD-1 inhibitor. Results: Of 189 patients, 24 (13%; 13 males; 60.5 ± 12.2 years) presented with IIH at a median of 16.1 (range: 6.7–160) weeks after commencing treatment, occurring in 14 (58%) after the fourth infusion. At the presentation of IIH, corticotroph deficiency was characterised by an acute and severe decrease in cortisol levels to ≤83 nmol/L (≤3 μg/dL) in all patients, often only days after a previously recorded normal cortisol level. Free thyroxine (fT4) levels were observed to decline from 12 weeks prior to the onset of cortisol insufficiency, with the recovery of thyroid hormone levels by 12 weeks after the presentation of IIH. A median fall in fT4 level of 20% was observed at a median of 3 weeks (IQR: 1.5–6 weeks) prior to the diagnosis of IIH. Conclusion: IIH is characterised by an acute severe decline in cortisol levels to ≤83 nmol/L at presentation. A fall in fT4 can herald the development of ACTH deficiency and can be a valuable early indicator of IIH.